The relationship between severity of child abuse and disruptive behavior in adolescent males and females - Malone, Marisa Gloria (2013)
Conduct disorder is one of the most frequently diagnosed disorders for boys and girls under the age of 18. Although it is the second most common psychiatric disorder in girls, boys are much more likely to receive a conduct disorder diagnosis than girls. This gender difference in the prevalence rates of disruptive behavior disorders, such as conduct and oppositional defiant disorders, may be due to the underrepresentation of females in studies used to determine the diagnostic criteria of these disorders in the Diagnostic and Statistical Manual of Mental Disorders. Another reason could be because females tend to display more covert forms of aggression and misconduct, whereas males often show more physical or instrumental forms. Males are highly overrepresented, potentially making it less likely for females to receive a diagnosis of conduct or oppositional defiant disorder, even when they display aggressive and delinquent behaviors. As females with CD are susceptible to several comorbid psychological diagnoses, further research is essential for diagnostic and treatment purposes. The purpose of the current study was to further define any gender differences in aggressive behaviors in males and females and to look at the relationship between the experience of varying levels of child abuse and aggressive and disruptive behavior. The current study used archival data derived from a sample of adolescents in addiction treatment programs or juvenile detention centers who were evaluated for disruptive behavior disorders and co-occurring conditions using a structured diagnostic interview (Practical Adolescent Dual Diagnosis Interview, Estroff & Hoffmann, 2000). Participants in this sample include 571 adolescents (445 males and 71 females) from juvenile justice settings and 338 adolescents (126 males and 262 females) from addiction treatment programs. Due to differences between the juvenile justice and addiction treatment populations, all analyses were conducted separately by group. Results suggest that males and females in juvenile justice settings are similar in their presentation of aggressive and disruptive symptoms; however, in the addiction treatment setting, males displayed more disruptive behavior. Results also suggest that greater experience of abuse was related to an increased number of disruptive behavior symptoms, although there were some gender and facility differences. This study further adds to the dearth of literature regarding the relationship between experiencing several types of child abuse and increased externalizing behavior, as well as provides additional information regarding gender differences in the manifestation of disruptive behavior symptoms.